Do Brain-Derived Neurotrophic Factor Genetic Polymorphisms Modulate the Efficacy of Motor Cortex Plasticity Induced by Non-invasive Brain Stimulation? A Systematic Review - Sasaki, Ryoki; Kojima, Sho; Onishi, Hideaki (Frontiers in Human Neuroscience, 2021)
Techniques of noninvasive brain stimulation (NIBS) of the human primary motor cortex (M1) are widely used in basic and clinical research to induce neural plasticity. The induction of neural plasticity in the M1 may improve motor performance ability in healthy individuals and patients with motor deficit caused by brain disorders. However, several recent studies revealed that various NIBS techniques yield high interindividual variability in the response, and that the brain-derived neurotrophic factor (BDNF) genotype (i.e., Val/Val and Met carrier types) may be a factor contributing to this variability. Here we conducted a systematic review of all published studies that investigated the effects of the BDNF genotype on various forms of NIBS techniques applied to the human M1. The motor-evoked potential (MEP) amplitudes elicited by single-pulse transcranial magnetic stimulation, which can evaluate M1 excitability, were investigated as the main outcome. A total of 1827 articles were identified, of which 17 (facilitatory NIBS protocol, 27 data) and 10 (inhibitory NIBS protocol, 14 data) were included in this review. More than two-thirds of the data (70.4%–78.6%) on both NIBS protocols did not show a significant genotype effect of NIBS on MEP changes. Conversely, most of the remaining data revealed that the Val/Val type is likely to yield a greater MEP response after NIBS than the Met carrier type in both NIBS protocols (21.4%–25.9%). Finally, to aid future investigation, we discuss the potential effect of the BDNF genotype based on mechanisms and methodological issues.